Innovative Approaches to Higher Education and Training for Sustainable Quality and Standardization of University Education for Sustainable Development in Kenya - Okebiro, Gilbert N. (Machakos University, 2018)
Education is a key for better life and effective foundation for smooth operations of person’s lifetime. In the recent times university education is becoming irrelevant for hiring the individuals, in organizations and industries both locally, nationally and internationally. This is due to graduates from unfettered proliferation of Satellite University campuses in almost every town in Kenya churning half baked graduates. The problem is the commercialization and politicization of higher education leading to poor standards and quality education leading churning out unemployable graduates trained courses which are unresponsive to market needs and industrial attraction. The objective is to investigate whether the satellite campuses offer courses with quality and standards. The paper employs a survey method and data collected through questionnaires from students in satellite campuses in Kitale town through simple random sampling. The research paper target a population of 500 and 30% sample size. The key results shows that there is poor standards in satellite campuses because part time lecturers are not paid on time and wait for three years and lead to de-motivation as a consequence of poor teaching and supervision of students. Some lecturers do not submit the marked scripts and the management manipulate grades for students to graduate. There is insufficient and dilapidated infrastructure, boated enrolment, nepotism, tribalism and poor quality education offered in satellite campuses. It is concluded the emergency of university satellite campuses has led to poor quality and standards in universities leading to half-baked and unemployable graduates though having attractive grades. The research paper recommends innovate approaches should be used for education reforms and restructuring be done in satellite campuses for sustainable education development inline with vision 2030.The satellite campuses should be allowed to operate if they have enough and full time qualified teaching staff and finances, without which standards of higher education will remain poor in Kenya.
Keywords: Education